Grindcore as a Medium of Social Critique: A Study of AK//47 in the Underground Music Scene in Semarang (1999–2016): Grindcore sebagai Media Kritik Sosial: Studi tentang AK//47 dalam Skena Musik Underground di Semarang (1999–2016) - Chrisnanda, David Yudha; Carolina Santi Muji Utami (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
This study aims to analyze the development of the underground music scene in Semarang during the period 1999–2016, with a particular focus on the role of AK//47 in utilizing grindcore music as a medium for social criticism. This study uses a historical method that includes the stages of heuristics, source criticism, interpretation, and historiography. Data collection techniques include literature review, archival analysis, and in-depth interviews with relevant informants. The findings show that AK//47 not only played a significant role in the formation and development of the underground music scene in Semarang, but also positioned grindcore music as a medium for expressing dissatisfaction with social, political, and environmental issues. This study demonstrates that grindcore, with its inherent Do It Yourself (DIY) ethos, functions as a means of cultural resistance and grassroots advocacy. It is hoped that this research will enrich the historiography of local music in Indonesia, particularly regarding the dynamics of underground subcultures as spaces for social and political articulation.